Customer Satisfaction Survey: Inputs to Improved Delivery of National Tobacco Administration Services - Marifel D. Ancheta; Tiffany Ruth R. Quinitip; Daniel B. Gacayan (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Customer satisfaction survey serves as one of the monitoring tools to measure how the National Tobacco Administration (NTA) relate with their customers, as this provides tangible and verifiable data on how NTA deliver its services. This survey aimed at measuring customer satisfaction with their 1) transaction with NTA, 2) availed services, and 3) execution of services for the year 2021 particularly the Tobacco Contact Growing System (TCGS). The TCGS promotes a market-oriented approach in tobacco production through the adoption of a contract-growing scheme, to enhance participation of the private sector in production technology transfer, credit assistance, and leaf marketing. Data were gathered through face-to-face and telephone interviews conducted among 500 farmers and 100 stakeholders, respectively, and were analyzed using frequency, percentage, median, and Spearman correlation coefficient. Findings reveal that almost all respondents in both customer groups are very satisfied with NTA services, policies, systems and procedures.